Potential of nightsky nocturnal radiative cooling as a fresh produce preservation method - Gikuru, Mwithiga; Kirui, Anthony C. (My University, 2007)
Abstract: The change in water temperature in horizontally placed pans exposed to the night-sky radiation was monitored at night between the hours of 8:00pm and 6:00am. The effect of varying the quantity of water in the pan was studied by varying the depth (1.0, 1.5, 2.0, 2.5 and 3.0mm) while effect of surface color of radiating surface was determined by placing two different coloured pans adjacent to each other. The effectiveness of this method in capturing “cold load” and the possible use of this cold energy for daytime preservation of fresh produce is analyzed and discussed. It was found that the water in the pan could be cooled to a temperature that was 9 oC below the lowest ambient dry bulb temperature. Also, the black painted surfaces cooled the water at higher rates than white surfaces and ultimately attained much lower temperatures in the long run. Within the experimental water loading depth range of 1-3 mm, the shallower depths attained lower final cold water temperature but had lower cooling efficiency in terms of total peak cold load per unit area of pan surface. The authors have shown that each square metre of pan surface can store enough “cold load” to remove the heat of respiration of a 10 kg load of vegetables or fruits that is maintained at or below the lowest ambient night dry bulb temperature. The fresh produce so maintained can therefore be about 10-15 oC below recorded daytime dry bulb temperature in the tropics which is sufficient to double the shelf life of most fresh produce commodities.
Keywords: Nightsky radiation; Cooling; Temperature difference; Cold load; Shelf life